MOLECULAR IDENTIFICATION OF SOME SEEDLING OF DATE PALM (Phoenix dactylifera L.) MALES’ TREES - S. A. Seif El-Yazal; H. F. Alharby; M. A. Seif El-Yazal; G. M. Hassan; M. M. Rady (Journal of Animal and Plant Sciences, 2017)
The present investigation was conducted during the season of 2014 using five seedlings of date palm males selected from the evaluation of fifty male seedlings of date palm grown in Tamiya district, Fayoum Governorate, Egypt. To facilitate the selection and identification of good male pollinators for further using in breeding programs, the selection was carried out for promising males to be used to pollinate the females of date palm. The selected five male seedlings of date palm were analyzed using RAPD marker. Among a total of 77 bands obtained, 75 bands were polymorphic and the other 2 bands were monomorphic. Amplification size ranged between 280 and 2000 bp. UPGMA based cluster diagram showed that the all five different genotypes were grouped into two major clusters. Polymorphism percentage (96.4%) was indicated a high genetic diversity among the date palm studied.
Keywords: Date palm males; Genetic diversity; RAPD markers